Vision to implementation gap in a Thai organizational learning context: HRD opportunities for leaders - Meksang, S.; Whiteley, Alma (Intellectbase International Consortium ( IIC ), 2012)
Although vision is well accepted as a critical component in both leadership and performance there is little research on the implementation of learning organization visions. No such research has been reported in the Thai context. The paper reports on a study of private sector organizations in Thailand. It set out to explore factors surrounding enablers and inhibitors to the construction and maintenance of a learning organization and central to this, the connection of vision to its implementation. For research purposes this revolved around the ability of leaders (senior managers), managers and staff to sustain the personal and organizational growth implied in vision statements. The data showed more an 'exploitation' than 'exploration' learning strategy (March, 1991), where learning was mediated by control and performance management systems. The received practice conceptual framework presents developmental opportunities for (Thai) managers. This will include 'learning' the vision rhetoric, researching employees' epistemic lenses and gathering data on vision statements as received by employees. Where the received vision statement is congruent with the espoused vision statement, the next developmental task is to check that formal learning and performance arrangements do not divert employees towards, safe, performing learning activities (Bandura, 1978).